2022
DOI: 10.3389/fpls.2022.713481
|View full text |Cite
|
Sign up to set email alerts
|

Too Dense or Not Too Dense: Higher Planting Density Reduces Cannabinoid Uniformity but Increases Yield/Area in Drug-Type Medical Cannabis

Abstract: A major challenge for utilizing cannabis for modern medicine is the spatial variability of cannabinoids in the plant, which entail differences in medical potency. Since secondary metabolism is affected by environmental conditions, a key trigger for the variability in secondary metabolites throughout the plant is variation in local micro-climates. We have, therefore, hypothesized that plant density, which is well-known to alter micro-climate in the canopy, affects spatial standardization, and concentrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 70 publications
(91 reference statements)
0
4
0
Order By: Relevance
“…In many species, variation in light penetration has been shown to contribute to intra‐plant variation in secondary metabolites, including: flavonoids (Del Valle et al, 2018 ), anthocyanins (González‐Talice et al, 2013 ), and tannins (Mole et al, 1988 ). Recently, Danziger and Bernstein ( 2022 ) found that increased shading as a result of greater planting density decreased cannabinoid concentrations in axillary inflorescences from the bottom of the plant. Additional work examining light penetration into the canopy, photosynthetic activity throughout the canopy, and sub‐canopy lighting will provide a better understanding of the degree to which variability in light intensity modulates variation in cannabinoid concentration.…”
Section: Discussionmentioning
confidence: 99%
“…In many species, variation in light penetration has been shown to contribute to intra‐plant variation in secondary metabolites, including: flavonoids (Del Valle et al, 2018 ), anthocyanins (González‐Talice et al, 2013 ), and tannins (Mole et al, 1988 ). Recently, Danziger and Bernstein ( 2022 ) found that increased shading as a result of greater planting density decreased cannabinoid concentrations in axillary inflorescences from the bottom of the plant. Additional work examining light penetration into the canopy, photosynthetic activity throughout the canopy, and sub‐canopy lighting will provide a better understanding of the degree to which variability in light intensity modulates variation in cannabinoid concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Arsenault et al (2024) also evaluated Δ 9-THC and total CBD in 14 cultivars of hemp, demonstrating that both CBD and THC increase rapidly over a 1-2-week time frame with maximum concentrations (about 16% and 0.6%, respectively). However, the increase in THC and CBD in C. sativa is not yet defined, it is known to be related to soilclimatic conditions and even the availability of nutrients (Danziger andBernstein, 2022, Saloner and.…”
Section: Cannabinoid Contentsmentioning
confidence: 99%
“…The biological effect of cannabis Fleisher-Berkovich et al Journal of Cannabis Research (2024) 6:25 cultivar extracts may therefore have higher efficacy compared to treatments with only individual cannabinoids (Comelli et al 2008). The production of bioactive compounds in the cannabis plant is affected by genetics (Shiponi & Bernstein 2021b), location in the plant (Bernstein et al 2019), and by cultivation conditions Bernstein 2021, 2022a;Danziger and Bernstein 2022). Since the secondary metabolite profile in cannabis varies between plant cultivars (Danziger & Bernstein 2021a;Saloner & Bernstein 2022b), so may their beneficial effects against neuroinflammation.…”
Section: Introductionmentioning
confidence: 99%